Coating for negative electrode and solid-state battery comprising same
By using a coating containing element A that can be alloyed with lithium and element B that cannot be alloyed with lithium on the anode of the all-solid state battery, combined with carbonaceous materials, the problem of lithium metal anode forming lithium dendrites in the all-solid state battery is solved, achieving a longer cycle life and higher safety.
Patent Information
- Application Number
- CN202480003711.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-04-22
- Publication Date
- 2025-03-28
AI Technical Summary
Lithium metal anode is prone to form lithium dendrites in all-solid-state batteries, resulting in safety problems and short cycle life. Although the Ag/C nanocomposite layer in the prior art can improve cycle life, it may accelerate the growth of lithium dendrites and affect safety.
An anode coating containing two elements (A and B) and carbonaceous materials is used, in which element A can be alloyed with lithium, while element B cannot be alloyed with lithium. By optimizing the weight ratio of elements A and B and the volume percentage of carbonaceous materials, the agglomeration of element A is avoided and the conductivity and stability of the coating is improved.
It realizes improving cycle life and safety in all-solid-state batteries, reducing battery cell resistance, improving specific capacity and capacity retention rate, and significantly reducing charging overpotential.
Smart Images

Figure CN119731791A_ABST
Abstract
Description
[0001] Cross-references
[0002] This application claims priority to U.S. Serial No. 63 / 517,364, filed on August 3, 2023, and U.S. Serial No. 63 / 498,545, filed on April 27, 2023, the entire contents of which are incorporated by reference into this application. Technical Field
[0003] The present disclosure relates to a coating comprising two elements (A and B) and a carbonaceous material, wherein element A is capable of alloying with lithium and element B is not capable of alloying with lithium. A solid-state battery comprising the coating is also disclosed. Background Art
[0004] Lithium metal anodes are more promising for high energy density all-solid-state batteries (ASSBs) than other kinds of anodes such as graphite-based anodes due to their theoretical capacity (3,860 mAh / g). However, the formation of lithium dendrites may lead to safety issues and result in short cycle life. It has been shown that Ag / C nanocomposite layers on lithium metal anodes can lead to improved cycle life. Silver nanoparticles tend to form agglomerates and may worsen safety issues by accelerating the growth of lithium dendrites. Therefore, a new anode design is still needed. Summary of the invention
[0005] The present disclosure provides an anode coating (or, layer) comprising two elements (A and B) and a carbonaceous material, wherein element A is capable of alloying with lithium and element B is not capable of alloying with lithium. Also disclosed are a method for preparing the anode coating and an all-solid-state battery (ASSB) comprising the anode coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] Non-limiting embodiments of the present disclosure will be described by way of example with reference to the accompanying drawings, which are schematic and are not intended to be drawn to scale. In the accompanying drawings, each identical or nearly identical component shown is generally represented by a single numeral. For clarity, not every component is labeled in every drawing, nor is every component of every embodiment of the present disclosure shown, where illustration is not necessary to allow one of ordinary skill in the art to understand the present disclosure.
[0007] Figure 1 is a schematic diagram showing a coating ( 1 ) comprising particles of element A ( 2 ), particles of element B ( 3 ), and a carbonaceous material ( 4 ) on an anode current collector ( 5 ) according to one embodiment of the present disclosure.
[0008] Figure 2is a schematic diagram showing a coating layer (1) comprising particles of element A (2), particles of element B (3) and a carbonaceous material (4) on an anode active material layer (6) comprising lithium metal according to one embodiment of the present disclosure.
[0009] Figure 3 The rate capabilities of batteries comprising coatings of Reference Example (Ref. Ex), Comparative Example 1 (Comp. Ex 1), Comparative Example 2 (Comp. Ex 2), Comparative Example 3 (Comp. Ex 3), Example 1 (Ex 1), Example 2 (Ex 2), Example 3 (Ex 3), Example 4 (Ex 4), Example 5 (Ex 5), and Example 6 (Ex 6) according to some embodiments of the present disclosure are shown.
[0010] Figure 4 The discharge capacity cycle performance of batteries including coatings of Reference Example (Ref. Ex), Comparative Example 1 (Comp. Ex 1), Comparative Example 2 (Comp. Ex 2), Comparative Example 3 (Comp. Ex 3), Example 4 (Ex 4), and Example 5 (Ex 5) according to some embodiments of the present disclosure are shown.
[0011] Figure 5 A SEM image of a coating layer including Ag / C prepared according to Reference Example is shown.
[0012] Figure 6 An SEM image of a coating layer including Zn as element A, Cu as element B, and a carbonaceous material according to Example 4 is shown.
[0013] Figure 7 The electrochemical impedance spectroscopy (EIS) results of the reference example (Ref. Ex) and example 4 (Ex 4) before and after the rate performance test are shown.
[0014] Figure 8 A half-cell test showing high c-rate performance up to 5.5C (1C=170 mAh) of Example 5 according to one embodiment of the present disclosure relative to a reference example.
[0015] Fig. 9 A half-cell test of the cycle performance based on 0.33C (1C=170 mAh) of Example 5 according to one embodiment of the present disclosure relative to a reference example is shown. DETAILED DESCRIPTION
[0016] Disclosed herein is a coating that provides desired cycle life and safety benefits when incorporated into an all-solid-state battery. In some embodiments, the coating (or alternatively, a layer) comprises at least two metal or metalloid elements (A and B) and a carbonaceous material, wherein element A is capable of alloying with lithium and element B is not capable of alloying with lithium. In some embodiments, the coating disclosed herein is a coating for a negative electrode such as an anode. In some embodiments, the coating is an interfacial layer between a negative electrode and an electrolyte in an electrochemical device. In some embodiments, the coating is in direct contact with an anode current collector or an anode active material layer of the anode or negative electrode. As used herein, an "anode" may be an anode current collector, an anode active material layer, or a combination of both. For example Figure 1 As shown, the coating (1) includes particles (2) of element A capable of alloying with lithium and particles (3) of element B not capable of alloying with lithium dispersed in a carbonaceous material (4). Figure 1 As shown, the coating (1) can be disposed on the anode current collector (5). In other embodiments, as Figure 2 As shown, the coating (1) may be disposed on a layer (6) of an anode active material, such as lithium metal, which in turn is disposed on an anode current collector (5).
[0017] In some embodiments, the carbonaceous material comprises at least one selected from the group consisting of carbon fiber, carbon nanotube, carbon wire, natural graphite, artificial graphite, graphene, carbon black, acetylene black and Ketjen black. In some embodiments, the carbonaceous material is presented in a form selected from the group consisting of nanoparticles, nanosheets, nanowires, nanotubes and combinations thereof. In some embodiments, at least one dimension of the nanoparticles, nanosheets, nanowires and nanotubes is less than or equal to 100nm. In some embodiments, the volume percentage of the carbonaceous material in the coating is not less than 50%.
[0018] In some embodiments, element A is selected because of its ability to form alloys with lithium atoms or ions, so it can be alloyed with lithium. In some embodiments, element A and lithium can form an alloy, wherein the weight percentage of lithium in the alloy is greater than or equal to 4%, 10%, 15%, 20%, 25%, or 30%. In some embodiments, element A and lithium can form an alloy, wherein the weight percentage of lithium in the alloy is less than or equal to 50%, 40%, 30%, 20%, or 10%.
[0019] In some embodiments, element A is a metal or a metalloid. In some embodiments, element A is at least one selected from the group consisting of Ag, Zn, Ti, Cd, Mg, Al, Ga, Si, Ge, In, Sn, Pb, Bi, Sb and mixtures thereof. In some embodiments, element A does not contain Ag. In some embodiments, when the coating is arranged on the anode, because of the accumulation of lithium in the anode active material and / or lithium at the anode during charging, particles of element A may migrate or move in the carbonaceous material over time to concentrate or agglomerate in an area adjacent to the anode or even in the anode. Excessive agglomeration of particles of element A may lead to the formation of lithium dendrites and a shortage of battery cells, so in some embodiments, the weight percentage of element A is less than or equal to 17.5% of the coating. In some embodiments, the weight percentage of element A in the coating is in the following ranges: 1% to 17.5%, 2.5% to 17.5%, 5% to 17.5%, 7.5% to 17.5%, 1% to 15%, 2% to 15%, 3% to 15%, 4% to 15%, 5% to 15%, 7.5% to 15%, 1% to 12.5%, 2% to 12.5%, 3% to 12.5%, 5% to 12.5%, 7.5% to 12.5%, 1% to 10%, 2% to 10%, 3% to 10%, 5% to 10%, 7.5% to 10% and any and all ranges and subranges therebetween. In some embodiments, element A may also be an elementary compound capable of alloying with lithium, such as a silicon compound and a tin alloy. In some embodiments, the silicon compound may be SiO x (wherein 0.5≤x≤1.5). In some embodiments, non-limiting specific tin alloys include Cu—Sn alloys and Co—Sn alloys, etc. In some embodiments, when a cross section of the coating is observed using a SEM, the coating has no agglomeration of element A and element B.
[0020] In some embodiments, element B is selected because of its ability to not form alloys with lithium ions or atoms, and therefore it cannot alloy with lithium. Without being bound by theory, it is believed that because element B cannot alloy with lithium, particles of element B do not migrate or agglomerate within the carbonaceous material like element A. In some embodiments, the conductivity of element B is higher than the conductivity of the carbonaceous material and / or element A, thereby enhancing the conductivity of the coating.
[0021] In some embodiments, element B is at least one selected from the group consisting of Cu, Mo, Ir, W, Co, Ni, Ru, Fe, Se, Ta, Nb, V, Zr, and mixtures thereof. In some embodiments, the weight percentage of element B in the coating is in the range of 3% to 15%. In some embodiments, the weight percentage of element B in the coating is in the range of 1% to 17.5%, 2.5% to 17.5%, 5% to 17.5%, 7.5% to 17.5%, 1% to 15%, 2% to 15%, 3% to 15%, 4% to 15%, 5% to 15%, 7.5% to 15%, 1% to 12.5%, 2% to 12.5%, 3% to 12.5%, 5% to 12.5%, 7.5% to 12.5%, 1% to 10%, 2% to 10%, 3% to 10%, 5% to 10%, 7.5% to 10%, and any and all ranges and subranges therebetween.
[0022] In some embodiments, the conductivity of element B is higher than the conductivity of element A to increase the conductivity of the coating. In some embodiments, the ratio of the conductivity of element B to the conductivity of element A is in the range of 1 to 30, 2.5 to 30, 5 to 30, 10 to 30, 1 to 25, 2.5 to 25, 5 to 25, 10 to 25, 1 to 20, 2.5 to 20, 5 to 20, 10 to 20, 1 to 15, 2.5 to 15, 5 to 15, 10 to 15, 1 to 10, 2.5 to 10, 5 to 10, and any and all ranges and sub-ranges therebetween. In some embodiments, the ratio of the conductivity of element B to the conductivity of element A is less than 1. In some embodiments, the ratio of the conductivity of element B to the conductivity of element A is in the range of 0.2 to 1.0, 0.5 to 1.0, or 0.75 to 1.0.
[0023] In some embodiments, the weight ratio of element A to element B is in the range of 1:99 to 50:50. In some embodiments, the weight ratio of element A to element B is in the range of 1:99 to 50:50, 2:98 to 50:50, 3:97 to 50:50, 4:96 to 50:50, 5:99 to 50:50, 7.5:92.5 to 50:50, 10:90 to 50:50, 15:85 to 50:50, 20:80 to 50:50, 1:99 to 55:45, 2:98 to 55:45, 3:97 to 55:45, 4:96 to 55:45, 5:9 :40, 10:90 to 60:40, 15:85 to 60:45, 20:80 to 55:45, 1 :99 to 60:40, 2:98 to 60:40, 3:97 to 60:40, 4:96 to 60:40, 5:95 to 60:40, 7.5:92.5 to 60:40, 10:90 to 60:40, 15:85 to 60:40, 20:80 to 60:40 and any and all ranges and subranges therebetween.
[0024] In some embodiments, the total weight percentage of elements A and B in the coating (element A wt% + element B wt%) is in the range of 5% to 20% in the coating. In some embodiments, the total weight percentage of elements A and B is in the range of 1% to 30%, 1% to 25%, 1% to 20%, 1% to 15%, 1% to 12.5%, 1% to 10%, 2.5% to 30%, 2.5% to 20%, 2.5% to 15%, 2.5% to 10%, 5% to 30%, 5% to 25%, 5% to 20%, 5% to 15%, 5% to 10%, 7.5% to 30%, 7.5% to 25%, 7.5% to 20%, 7.5% to 15%, 7.5% to 10%, 10% to 30%, 10% to 25%, 10% to 20%, 10% to 15%, and any and all ranges and subranges therebetween.
[0025] In some embodiments, the total volume percentage of elements A and B (element A vol% + element B vol%) in the coating is in the range of 1% to 15%. In some embodiments, the total volume percentage of elements A and B in the coating is in the range of 1% to 25%, 1% to 20%, 1% to 15%, 1% to 12.5%, 1% to 10%, 2.5% to 20%, 2.5% to 15%, 2.5% to 10%, 5% to 25%, 5% to 20%, 5% to 15%, 5% to 10%, 7.5% to 25%, 7.5% to 20%, 7.5% to 15%, 7.5% to 10%, 10% to 25%, 10% to 20%, 10% to 15%, and any and all ranges and subranges therebetween.
[0026] In some embodiments, element A, element B or both may be in the form of nanoparticles in the coating. In such embodiments, the average particle size (D50) of the nanoparticles may be in the range of 20nm to 80nm. In some embodiments, the average particle size is in the range of 10nm to 200nm, 10nm to 175nm, 10nm to 150nm, 10nm to 125nm, 10nm to 100nm, 10nm to 80nm, 10nm to 60nm, 10nm to 50nm, 15nm to 200nm, 15nm to 175nm, 15nm to 150nm, 15nm to 125nm, 15nm to 100nm, 15nm to 80nm, 15nm to 60nm, 15nm to 50nm, 15nm to 200nm, 15nm to 175nm, 15nm to 150nm, 15nm to 125nm, 15nm to 100nm, 15nm to 80nm, 15nm to 60nm, 15nm to 50nm nm to 50 nm, 20 nm to 200 nm, 20 nm to 175 nm, 20 nm to 150 nm, 20 nm to 125 nm, 20 nm to 100 nm, 20 nm to 80 nm, 20 nm to 60 nm, 20 nm to 50 nm, 25 nm to 200 nm, 25 nm to 175 nm, 25 nm to 150 nm, 25 nm to 125 nm, 25 nm to 100 nm, 25 nm to 80 nm, 25 nm to 60 nm, and any and all ranges and subranges therebetween.
[0027] In some embodiments, the thickness of the coating is in the range of 0.1 μm to 50 μm. In some embodiments, the thickness of the coating is in the range of 0.05 μm to 100 μm, 0.1 μm to 100 μm, 0.25 μm to 100 μm, 0.5 μm to 100 μm, 1 μm to 100 μm, 2.5 μm to 100 μm, 5 μm to 100 μm, 10 μm to 100 μm, 0.05 μm to 75 μm, 0.1 μm to 75μm, 0.25μm to 75μm, 0.5μm to 75μm, 1μm to 75μm, 2.5μm to 75μm, 5μm to 75μm, 10μm to 75μm, 0.1μm to 50μm, 0.25μm to 50μm, 0.5μm to 50μm, 1μm to 50μm, 2.5μm to 50μm, 5μm to 5 0μm, 10μm to 50μm, 0.05μm to 25μm, 0.1μm to 25μm, 0.25μm to 25μm, 0.5μm to 25μm, 1μm to 25μm, 2.5μm to 25μm, 5μm to 25μm, 10μm to 25μm, 0.05μm to 20μm, 0.1μm to 20μm, 0.25μm to 20μm, 0.5μm to 20μm, 1μm to 20μm, 2.5μm to 20μm, 5μm to 20μm, 10μm to 20μm, 0.05μm to 10μm, 0.1μm to 10μm, 0.25μm to 10μm, 0.5μm to 10μm, 1μm to 10μm, 2.5μm to 10μm or 5μm to 10μm.
[0028] In some embodiments, the coating may also include a binder. The binder may be a polymer. In some embodiments, the binder may be selected from at least one of the groups consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride / hexafluoropropylene copolymer, polyimide, polyethylene, polyester, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose / styrene-butadiene rubber (CMC / SBR) copolymer, styrene-butadiene rubber (SBR) and mixtures thereof. In some embodiments, the weight percentage of the binder in the coating is in the range of 1% to 20%. In some embodiments, the weight percentage of the binder in the coating is in the following ranges: 1% to 15%, 1% to 10%, 1% to 7.5%, 1% to 5%, 2% to 15%, 2% to 10%, 2% to 7.5%, 2% to 5%, 2.5% to 15%, 2.5% to 10%, 1.5% to 7.5%, 2.5% to 5% and any and all ranges and sub-ranges therebetween.
[0029] In some embodiments, the coating may further include a dispersant. In some embodiments, the dispersant may be at least one selected from the group consisting of polyvinyl pyrrolidone (PVP), ethyl cellulose, polyethylene glycol, and mixtures thereof. In some embodiments, the weight percentage of the dispersant in the coating is in the range of 0.01% to 5%. In some embodiments, the weight percentage of the dispersant in the coating is in the following ranges: 0.01% to 10%, 0.01% to 7.5%, 0.01% to 5%, 0.01% to 2.5%, 0.01% to 1%, 0.01% to 0.5%, 0.01% to 0.25%, 0.02% to 10%, 0.02% to 7.5%, 0.02% to 5%, 0.02% to 2.5%, 0.02% to 1%, 0.02% to 0.5%, 0. .02% to 0.25%, 0.05% to 10%, 0.05% to 7.5%, 0.05% to 5%, 0.05% to 2.5%, 0.05% to 1%, 0.05% to 0.5%, 0.05% to 0.25%, 0.1% to 10%, 0.1% to 7.5%, 0.1% to 5%, 0.1% to 2.5%, 0.1% to 1%, 0.1% to 0.5%, 0.1% to 0.25%, and any and all ranges and subranges therebetween.
[0030] The present disclosure also provides a composition for preparing a coating. The composition may include multiple particles of element A, multiple particles of element B, a carbonaceous material and a binder. In some embodiments, the composition may also include a solvent and / or a dispersant. In some embodiments, a first plurality of particles of element A and a second plurality of particles of element B and the carbonaceous material are dispersed in a mixture comprising a solvent, a dispersant and a binder.
[0031] In some embodiments, the coating can be prepared from a composition / mixture. The method may include: (i) mixing a plurality of particles of element A, a plurality of particles of element B, a carbonaceous material, a binder, a solvent, and a dispersant into a mixture; (ii) applying the mixture to a substrate, and (iii) drying the mixture applied to the substrate to form a coating comprising particles of element A and particles of element B distributed therein. In some embodiments, the method further includes calendering the coated substrate during or after the mixture applied to the substrate is dried to ensure a uniform surface of the coating.
[0032] In some embodiments, the weight ratio of the solvent and dispersant to the element A, element B and binder in the mixture (ratio of (solvent+dispersant):(element A+element B+binder)) is in the range of 1:9 to 1:10.
[0033] In some embodiments, the mixture coated on the substrate is dried in air or an inert gas.
[0034] In some embodiments, the mixture coated on the substrate is dried at a temperature in the range of 80°C to 130°C for a period of 8 hours to 48 hours.
[0035] In some embodiments, the mixture coated on the substrate is further dried under vacuum at a temperature in the range of 60° C. to 120° C. for a period of 8 hours to 48 hours.
[0036] In one aspect, the present disclosure provides an electrochemical device such as an all-solid-state battery, the all-solid-state battery comprising an anode having a coating as described herein. The electrochemical device may include a cathode, a solid electrolyte, a coating, and an anode, wherein the coating may be used as an interface layer between the solid electrolyte and the anode. In some embodiments, the anode includes an anode current collector. In some embodiments, the anode includes an anode active material layer comprising lithium metal and an anode current collector.
[0037] In some embodiments, the solid electrolyte comprises an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or both.
[0038] In some embodiments, the oxide-based solid electrolyte is at least one selected from the group consisting of: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2,0≤y<3)、BaTiO3、Pb(Zr x Ti 1-x )O3(PZT, 0≤a≤1), Pb 1- x La x Zr 1-y Ti y O3(PLZT)(0≤x<1,0≤y<1), Pb(Mg 1 / 3 Nb 2 / 3 )O3—PbTiO3 (PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li 1+x+y (Al a Ga 1-a ) x (Tib Ge 1-b ) 2-x Si y P 3- y O 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ a ≤ 1, 0 ≤ b ≤ 1), Li x La y TiO3(0 < x < 2, 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O—Al2O3—SiO2—P2O5—TiO2—GeO2, Li 3+x La3M2O 12 (M is at least one selected from the group consisting of Te, Nb, and Zr, and x is an integer from 1 to 10) and Li 3+x La3Zr 2-a M a O 12 , wherein M is at least one selected from Ga, W, Nb, Ta, and Al, 0 < a < 2, and x is an integer from 1 to 10.
[0039] In some embodiments, the sulfide-based solid electrolyte is at least one selected from the following: P2S5, Li2S—P2S5—LiX (where X is a halogen element), Li2S—P2S5—Li2O, Li2S—P2S5—Li2O—LiI, Li2S—SiS2, Li2S—SiS2—LiI, Li2S—SiS2—LiBr, Li2S—SiS2—LiCl, Li2S—SiS2—B2S3—LiI, Li2S—SiS2—P2S5—LiI, Li2S—B2S3, Li2S—P2S5—Z m S n (where m and n are each positive, and Z is one selected from Ge, Zn, and Ga), Li2S—GeS2, Li2S—SiS2—Li3PO4, Li2S—SiS2—Li p MO q (where p and q are each positive, and M is one selected from P, Si, Ge, B, Al, Ga, and In), Li 7-x PS 6-x Cl x (0 ≤ x ≤ 2), Li 7-x PS 6-x Br x (0 ≤ x ≤ 2) and Li 7-x PS 6-x I x (0 ≤ x ≤ 2).
[0040] In some embodiments, the cathode comprises a x MO2、Li x Ni 1-y-z Co y M1 z O2 and Li x Ni 1-y-z Mn y M2 z O2, wherein M is at least one selected from the group consisting of Ni, Co, Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn and rare earth elements, wherein M1 is at least one selected from the group consisting of Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, C r, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn and rare earth elements, wherein M2 is at least one selected from the group consisting of Co, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn and rare earth elements, wherein 0.95≤x≤1.1, 1-yz>0, 0 <y≤0.5,0≤z≤0.5。
[0041] In some embodiments, the electrochemical device exhibits at least 94% capacity retention after 20 cycles at a discharge rate of 0.33C.
[0042] In some embodiments, the electrochemical device exhibits at least 160 mAh·g after 20 cycles at a discharge rate of 0.33 C. -1 Specific capacity.
[0043] In some embodiments, the electrochemical device is a battery or a cell of a battery. In some embodiments, the electrochemical device is an all-solid-state battery.
[0044] In some embodiments, a battery cell comprising an anode coating as described herein can reduce the total battery cell resistance by not less than 20%, not less than 25%, not less than 30%, not less than 35%, not less than 40%, not less than 45%, not less than 50%, not less than 55%, not less than 60%, or not less than 65%, compared to a battery cell comprising Ag / C as the anode coating.
[0045] In some embodiments, a battery cell comprising an anode coating as described herein can reduce the charge overpotential by not less than 20%, not less than 25%, not less than 30%, not less than 35%, not less than 40%, not less than 45%, not less than 50%, not less than 55%, not less than 60%, not less than 65%, or not less than 70% at a C rate in the range of 1C to 5.5C compared to a battery cell comprising Ag / C as an anode coating or protective layer at the same C rate. In some embodiments, the C rate is in the following ranges: 5.5C to 6C, 5.5C to 7C, 5.5C to 8C, 5.5C to 9C, or 5.5C to 10C.
[0046] In some embodiments, the coating comprises Cu as element A and Zn as element B, wherein the weight ratio of Cu to Zn is 3:7, and the weight ratio of Cu and Zn to carbonaceous material is 5:95, and wherein the thickness of the coating is about 15-25 μm.
[0047] The present disclosure will be better understood by reference to the following experimental details, but those skilled in the art will readily appreciate that the specific experiments detailed are illustrative only and are not meant to limit the present disclosure as described herein and defined by the appended claims.
[0048] Example
[0049] Preparation of coated anode
[0050] Table 1 Composition of anode coating
[0051] Example ElementA Element B A / B / carbon black weight ratio Reference example Ag none 25 / 0 / 75 Comparative Example 1 Zn none 25 / 0 / 75 Comparative Example 2 none Cu 0 / 25 / 75 Comparative Example 3 none none 0 / 0 / 100 Example 1 Zn Cu 7.5 / 17.5 / 75 Example 2 Zn Cu 17.5 / 7.5 / 75 Example 3 Zn Cu 12.5 / 12.5 / 75 Example 4 Zn Cu 1.5 / 3.5 / 95 Example 5 Zn Cu 3 / 7 / 90 Example 6 Zn Cu 6 / 14 / 80
[0052] Nanoparticles of one or more metals with a particle size D50 of 40-60 nm and carbon black powder (D50 = 35 nm) were mixed in a weight ratio of 1:3 in N-methylpyrrolidone (NMP) (Sigma-Aldrich) containing 7 wt% polyvinylidene fluoride (PVDF, Solef). N-methylpyrrolidone was slowly added to the mixture under continuous stirring using a mixer (Thinky Corporation, AR-100) to prepare an anode slurry.
[0053] The slurry was then coated on a 10 μm thick SUS (stainless steel) foil using a rod coating method and dried in a convection oven at 80°C for 20 min. The obtained electrode was further dried at 120°C under vacuum for 12 h. The average thickness of the coating was 15 ± 2 μm. Anodes with a coating containing only carbon black were also prepared by following the same mixing process, except that element A or B was not present. Table 1 summarizes the composition of various anode coatings.
[0054] Battery assembly and testing
[0055] A cell comprising a coated anode, an NCA cathode having at least 80% cathode active material, and an Argyrodite-type solid electrolyte as electrolyte was assembled. The cell testing was performed in 2 consecutive steps. First, the rate performance was tested at a constant charge rate of 0.1C throughout the test period, and then the rate performance was tested at discharge rates of 0.33C, 1C, and 0.33C, respectively. The specific capacity results are shown in Tables 2 and Figure 3 shown.
[0056] Table 2 Discharge capacity of batteries containing anode coating
[0057]
[0058] Secondly, the cycling performance tests were performed continuously at 0.33C / 0.33C at 45°C. The voltage window given to these tests was between 2.5V and 4.2V (vs. Li / Li + ). During the entire test process, all battery cells were operated at 4 MPa. The specific capacity results of the reference example, comparative examples 1-3, and examples 4 and 5 are shown in Figure 4 middle.
[0059] like Figure 3 As shown, Examples 1-3 share the same weight percentage of carbonaceous material, and likewise, the total weight of elements A and B is also the same. Among Examples 1-3, Example 1 shows the highest specific capacity.
[0060] like Figure 3 As shown in Figure 2, Examples 4 and 5 are comparable to the reference example (Ag / C) in terms of high rate discharge performance (1C). In addition, Example 5 is not only comparable to the reference example in terms of capacity realization at 0.33C ( Figure 4 ), and also maintained well in terms of capacity retention up to 20 cycles. Without wishing to be bound by any theory, this can be attributed to the uniform dispersion of Zn and Cu nanoparticles in the anode coating, which are less likely to migrate toward the current collector than Ag nanoparticles. Figure 7 is an EIS result showing that Example 4 has a 50% lower total cell resistance than the Ag / C coating. The reduced cell resistance enables easier Li migration back and forth within the cell during cycling. In some embodiments, a cell comprising an anode coating as described herein can reduce the total cell resistance by not less than 20%, not less than 25%, not less than 30%, not less than 35%, not less than 40%, not less than 45%, not less than 50%, not less than 55%, not less than 60%, or not less than 65%, compared to a cell comprising Ag / C as an anode coating.
[0061] according to Figure 4The battery cells containing the anode coatings of the reference example, comparative example 3, example 4 and example 5 showed 133, 152, 155 and 166 mAh·g respectively after 20 cycles at 0.33 C as both the charge rate and the discharge rate. -1 In some embodiments, an electrochemical device comprising an anode coating as disclosed herein exhibits a higher specific capacity than an electrochemical device having an Ag / C nanocomposite as an anode coating or carbon as an anode coating. In some embodiments, an electrochemical device comprising an anode coating as disclosed herein exhibits a specific capacity that is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55% higher than an electrochemical device having an Ag / C nanocomposite as an anode coating. In some embodiments, an electrochemical device comprising an anode coating as disclosed herein exhibits a specific capacity that is 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40% or 45% higher than an electrochemical device having carbon as an anode coating.
[0062] Also like Figure 4 As shown, the battery cells comprising the anode coatings of the reference example, comparative example 3, example 4 and example 5 exhibited capacity retention rates of 74%, 86%, 92% and 94% respectively after 20 cycles at 0.33C as both the charge rate and the discharge rate. In some embodiments, the electrochemical device comprising the anode coating as disclosed herein exhibits a higher capacity retention rate than the electrochemical device comprising the Ag / C nanocomposite as the anode coating or carbon as the anode coating. In some embodiments, the electrochemical device comprising the anode coating as disclosed herein exhibits a capacity retention rate of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55% higher than the electrochemical device having the Ag / C nanocomposite as the anode coating. In some embodiments, an electrochemical device comprising an anode coating as disclosed herein exhibits a capacity retention that is 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40% or 45% higher than an electrochemical device having carbon as the anode coating.
[0063] Based on the above data from Example 4, the electrochemical device can have a coating with a thickness ranging from 15 μm to 25 μm, wherein Zn is used as element A, Cu is used as element B, and carbon black is used as carbonaceous material in a weight ratio of 1.5:3.5:95. In some embodiments, such an electrochemical device exhibits a capacity retention rate of at least 90% after 20 cycles at a charge rate and a discharge rate of 0.33C and / or exhibits a capacity retention rate of at least 155 mAh·g after 20 cycles at a charge rate and a discharge rate of 0.33C. -1 Specific capacity.
[0064] Also based on the above data from Example 5, the electrochemical device can have a coating with a thickness ranging from 15 μm to 25 μm, wherein Zn is element A, Cu is element B, carbon black is carbonaceous material, and the weight ratio of the three is 3:7:90. In some embodiments, such an electrochemical device exhibits a capacity retention rate of at least 90% after 20 cycles at a charge rate and a discharge rate of 0.33C and / or exhibits a capacity retention rate of at least 160 mAh·g after 20 cycles at a discharge rate of 0.33C. -1 Specific capacity.
[0065] The examples also show that agglomeration of element A, which could deteriorate the electrochemical performance of the battery, can be avoided in the coating. Figure 5 is a cross-sectional SEM image of the coating of the reference example and shows that some Ag nanoparticles (element A) exist as agglomerates. In contrast, Figure 6 : is a cross-sectional SEM image of the coating of Example 4 comprising Zn as element A, Cu as element B and carbonaceous material, showing that the average particle size of Zn nanoparticles and Cu nanoparticles is in the range of 20 nm to 80 nm and is uniformly distributed in the carbonaceous material without agglomeration.
[0066] Table 3 Absolute overpotential of reference example and embodiment 5 in half-cell rate performance test
[0067]
[0068] *: For charging (lithium deposition on the anode side in full cells), half cells were tested at 1, 2, 3, 5 and 5.5 C (1 C = 170 mAh) and 6 cycles were given at each C rate at 45 °C.
[0069] As shown in Table 3, for charging, the battery cell containing the Zn / Cu anode coating according to Example 5 exhibited a significantly reduced overpotential. Figure 8 As shown, for C-rates of 1C, 2C, 3C, 5C, and 5.5C, the battery cell containing Example 5 exhibited overpotentials of about -64mV, about -127mV, about -189mV, about -310mV, and about -334mV, respectively. However, for C-rates of 1C, 2C, 3C, 5C, and 5.5C, the battery cell containing the reference anode coating exhibited overpotentials of about -160mV, about -225mV, about -330mV, about -490mV, and about -493mV, respectively. Compared with the reference example, the absolute values of the charge overpotentials of Example 5 were reduced by 60%, 46.7%, 42.7%, 36.7%, and 32.4% for C-rates of 1C, 2C, 3C, 5C, and 5.5C, respectively.
[0070] While the Ag / C reference exhibits frequent micro-shortage behavior, which can be indicated by a sudden surge in charge capacity and a subsequent drop in coulombic efficiency, the cell containing the Zn / Cu anode coating is very stable during cycling at 1 / 3C. This phenomenon can be attributed to the agglomeration and migration of Ag nanoparticles. In the case of the Zn / Cu anode, this does not lead to micro-shortage behavior as in the reference, as the active material composition is optimized to minimize agglomeration and the inactive materials are uniformly dispersed without migration.
[0071] aspect
[0072] In a first aspect, the present disclosure provides a coating comprising:
[0073] Element A that can alloy with lithium;
[0074] · Element B that cannot alloy with lithium; and
[0075] Carbonaceous materials,
[0076] The volume percentage of the carbonaceous material in the coating is at least 50%.
[0077] In a second aspect according to the first aspect, the element A is a metal or a metalloid.
[0078] In a third aspect according to the first or second aspect, the element A is capable of forming an alloy with lithium, and wherein the weight percentage of the element lithium in the alloy is greater than or equal to 4%.
[0079] In a fourth aspect according to any of the preceding aspects, element A is at least one selected from the group consisting of Ag, Zn, Ti, Cd, Mg, Al, Ga, Si, Ge, In, Sn, Pb, Bi and Sb.
[0080] In a fifth aspect according to any of the preceding aspects, the weight percentage of element A in the coating is in the range of 1% to 10%.
[0081] In a sixth aspect according to any of the preceding aspects, the electrical conductivity of the element B is greater than the electrical conductivity of the carbonaceous material.
[0082] In a seventh aspect according to any of the preceding aspects, element B is at least one selected from the group consisting of Cu, Mo, Ir, W, Co, Ni, Ru, Fe, Se, Ta, Nb, V and Zr.
[0083] In an eighth aspect according to any of the preceding aspects, the weight percentage of element B in the coating is in the range of 3% to 15%.
[0084] In a ninth aspect according to the first aspect, the electrical conductivity of the element B is greater than the electrical conductivity of the element A.
[0085] In a tenth aspect according to any of the preceding aspects, a weight ratio of element A to element B is in the range of 1:99 to 50:50.
[0086] In an eleventh aspect according to any of the preceding aspects, the total weight percentage of element A and element B in the coating is in the range of 5% to 20%.
[0087] In a twelfth aspect according to any of the preceding aspects, in the coating element A, element B or both are in the form of nanoparticles, nanosheets, nanowires or nanotubes.
[0088] In a thirteenth aspect according to any of the preceding aspects, the average particle size (D50) of the nanoparticles is in the range of 20 nm to 80 nm.
[0089] In a fourteenth aspect according to the thirteenth aspect, the nanoparticles are not agglomerated in a cross section of the coating.
[0090] In a fifteenth aspect according to any of the preceding aspects, the coating has a thickness in the range of 0.1 μm to 50 μm.
[0091] In a sixteenth aspect according to any of the preceding aspects, the coating further comprises a binder.
[0092] In a seventeenth aspect according to any of the preceding aspects, the coating further comprises a dispersant.
[0093] In an eighteenth aspect, the present disclosure provides a composition for preparing a coating according to the first aspect. The composition comprises:
[0094] a first plurality of particles of element A,
[0095] a second plurality of particles of element B,
[0096] Carbonaceous materials, and
[0097] ·Binder.
[0098] In a nineteenth aspect according to the eighteenth aspect, the composition further comprises a solvent.
[0099] In a twentieth aspect according to the eighteenth or nineteenth aspect, the composition further comprises a dispersant.
[0100] In a twenty-first aspect according to the nineteenth aspect, the solvent is selected from the group consisting of N-methylpyrrolidone (NMP), tetrahydrofuran (THF), ethanol, distilled water, and a mixture thereof.
[0101] In a twenty-second aspect according to the twentieth aspect, the dispersant is at least one selected from the group consisting of polyvinylpyrrolidone (PVP), ethylcellulose, polyethylene glycol and a mixture thereof, and wherein the weight percentage of the dispersant in the composition is in the range of 0.01% to 5%.
[0102] In the twenty-third aspect according to any of the eighteenth to twenty-second aspects, the binder is at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride / hexafluoropropylene copolymer, polyimide, polyethylene, polyester, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose / styrene-butadiene rubber (CMC / SBR) copolymer, styrene-butadiene rubber (SBR) and mixtures thereof, and the weight percentage of the binder in the composition is in the range of 1% to 20%.
[0103] In a twenty-fourth aspect according to any of the eighteenth to twenty-third aspects, the carbonaceous material is at least one selected from the group consisting of carbon fiber, carbon nanotube, carbon wire, natural graphite, artificial graphite, graphene, carbon black, acetylene black, Ketjen black, and a mixture thereof.
[0104] In a twenty-fifth aspect, the present disclosure provides a method for preparing a coating, comprising:
[0105] a) mixing a plurality of particles of element A, a plurality of particles of element B, a carbonaceous material, a binder, a solvent and a dispersant into a mixture,
[0106] b) applying the mixture to a substrate, and
[0107] c) drying the mixture applied on the substrate to form a coating comprising particles of element A and particles of element B distributed therein,
[0108] Element A can alloy with lithium, and element B cannot alloy with lithium.
[0109] In a twenty-sixth aspect according to the twenty-fifth aspect, the method further comprises: calendering the coated substrate during or after the mixture coated on the substrate is dried.
[0110] In a twenty-seventh aspect according to the twenty-fifth or twenty-sixth aspect, a weight ratio of the solvent and dispersant to the element A, the element B and the binder is in a range of 1:9 to 1:10.
[0111] In a twenty-eighth aspect according to any one of the twenty-fifth to twenty-seventh aspects, the mixture coated on the substrate is dried in an inert gas.
[0112] In a twenty-ninth aspect, the present disclosure provides an electrochemical device comprising the coating according to any of the first to seventeenth aspects disposed on a negative electrode.
[0113] In a 30th aspect according to the 29th aspect, the negative electrode includes an anode current collector.
[0114] In a thirty-first aspect according to the twenty-ninth or thirtieth aspect, the negative electrode includes a layer of an anode active material including lithium metal.
[0115] In a thirty-second aspect according to any of the twenty-ninth to thirty-first aspects, the electrochemical device further comprises a solid electrolyte.
[0116] In a thirty-third aspect according to the thirty-second aspect, the solid electrolyte includes an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or both.
[0117] In a thirty-fourth aspect according to the thirty-third aspect, the oxide-based solid electrolyte is at least one selected from the group consisting of: Li 1+x+y Al x Ti 2-x Si y P 3-y O 12 (0 <x<2,0≤y<3)、BaTiO3、Pb(Zr x Ti 1-x )O3(PZT, 0≤a≤1), Pb 1-x La x Zr 1-y Ti y O3(PLZT)(0≤x<1,0≤y<1), Pb(Mg 1 / 3 Nb 2 / 3 )O3—PbTiO3 (PMN-PT), HfO2, SrTiO3, SnO2, CeO2, Na2O, MgO, NiO, CaO, BaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiO2, Li3PO4, Li x Ti y (PO4)3(0 <x<2,0<y<3)、Li x Al y Ti z (PO4)3(0 <x<2,0<y<1,0<z<3)、Li 1+x+y (Al a Ga 1-a ) x (Ti b Ge 1-b ) 2-x Si y P 3-yO 12 (0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ a ≤ 1, and 0 ≤ b ≤ 1), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li2O, LiOH, Li2CO3, LiAlO2, Li2O—Al2O3—SiO2—P2O5—TiO2—GeO2, Li 3+x La3M2O 12 (M is at least one selected from the group consisting of Te, Nb, and Zr, and x is an integer from 1 to 10), Li 3+x La3Zr 2-a M a O 12 , wherein M is at least one selected from Ga, W, Nb, Ta, and Al, 0 < a < 2, x is an integer from 1 to 10, and mixtures thereof.
[0118] In the thirty - fifth aspect according to the thirty - third aspect, wherein the sulfide - based solid electrolyte is at least one selected from the following: P2S5, Li2S—P2S5—LiX (where X is a halogen element), Li2S—P2S5—Li2O, Li2S—P2S5—Li2O—LiI, Li2S—SiS2, Li2S—SiS2—LiI, Li2S—SiS2—LiBr, Li2S—SiS2—LiCl, Li2S—SiS2—B2S3—LiI, Li2S—SiS2—P2S5—LiI, Li2S—B2S3, Li2S—P2S5—Z m S n (where m and n are each positive, and Z is one selected from Ge, Zn, and Ga), Li2S—GeS2, Li2S—SiS2—Li3PO4, Li2S—SiS2—Li p MO q (where p and q are each positive, and M is one selected from P, Si, Ge, B, Al, Ga, and In), Li 7-x PS 6-x Cl x (0 ≤ x ≤ 2), Li 7-x PS 6-x Br x (0 ≤ x ≤ 2), Li 7-x PS 6-x I x (0 ≤ x ≤ 2), and mixtures thereof.
[0119] In the thirty - sixth aspect according to any one of the twenty - ninth to thirty - fifth aspects, the electrochemical device further includes a cathode.
[0120] In a thirty-seventh aspect according to the thirty-sixth aspect, the cathode comprises a selected from the group consisting of LiFePO4, Li x MO2、Li x Ni 1-y- z Co y M1 z O2 and Li x Ni 1-y-z Mn y M2 z O2, wherein M is at least one selected from the group consisting of Ni, Co, Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn and rare earth elements, wherein M1 is at least one selected from the group consisting of Mn, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, C r, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn and rare earth elements, wherein M2 is at least one selected from the group consisting of Co, Al, B, Fe, Mg, Ca, Sr, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Rh, Pd, Cu, Zn, Cd, Ga, In, Sn and rare earth elements, wherein 0.95≤x≤1.1, 1-yz>0, 0 <y≤0.5,0≤z≤0.5。
[0121] In a thirty-eighth aspect according to any of the twenty-ninth to thirty-seventh aspects, the electrochemical device exhibits a capacity retention of at least 90% after 20 cycles at a discharge rate of 0.33C.
[0122] According to the 39th aspect of any of the 29th to 38th aspects, the electrochemical device exhibits at least 155 mAh·g after 20 cycles at a discharge rate of 0.33 C. -1 Specific capacity.
[0123] In the 40th aspect according to any of the 29th to 39th aspects, the electrochemical device exhibits a charge overpotential at a C rate in the range of 1C to 5.5C that is at least 30% lower than the charge overpotential of an electrochemical device comprising an anode coating comprising an Ag / C layer at the same C rate.
[0124] Various embodiments of the features of the present disclosure are described herein. However, it should be understood that these embodiments are provided only as examples, and that many changes, modifications and substitutions may be made by those skilled in the art without departing from the scope of the present disclosure. It should also be understood that various alternatives to the specific embodiments described herein are also within the scope of the present disclosure.
Claims
1. A coating comprising: Element A that can alloy with lithium; · Element B that cannot alloy with lithium; and Carbonaceous materials, The volume percentage of the carbonaceous material in the coating layer is at least 50%, and the element A is a metal or a metalloid. 2 . The coating according to claim 1 , wherein the element A is capable of forming an alloy with lithium, and wherein the weight percentage of the element lithium in the alloy is greater than or equal to 4%.
3. The coating according to claim 1, wherein the element A is at least one selected from the group consisting of Ag, Zn, Ti, Cd, Mg, Al, Ga, Si, Ge, In, Sn, Pb, Bi and Sb.
4. The coating according to claim 1, wherein the conductivity of the element B is greater than that of the carbonaceous material, and the element B is at least one selected from the group consisting of Cu, Mo, Ir, W, Co, Ni, Ru, Fe, Se, Ta, Nb, V and Zr. 5 . The coating according to claim 1 , wherein the weight percentage of the element A in the coating is in the range of 1% to 10%, and the weight percentage of the element B in the coating is in the range of 3% to 15%.
6. The coating according to claim 1, wherein the total weight percentage of the element A and the element B in the coating is in the range of 5% to 20%. The coating according to claim 1 , wherein the electrical conductivity of the element B is greater than the electrical conductivity of the element A. 8 . The coating according to claim 1 , wherein a weight ratio of the element A to the element B is in the range of 1:99 to 50:
50.
9. The coating of claim 1, wherein the element A, the element B, or both are in the form of nanoparticles, nanosheets, nanowires, or nanotubes in the coating.
10. The coating according to claim 9, wherein the nanoparticles are not agglomerated in a cross section of the coating, and an average particle size (D50) of the nanoparticles is in the range of 20 nm to 80 nm.
11. The coating according to claim 1, wherein the coating has a thickness in the range of 0.1 μm to 50 μm.
12. A method for preparing a coating, comprising: a) mixing a plurality of particles of element A, a plurality of particles of element B, a carbonaceous material, a binder, a solvent and a dispersant into a mixture, b) applying the mixture to a substrate, c) calendering the coated substrate during or after drying of the mixture coated on the substrate, and d) drying the mixture applied on the substrate to form a coating comprising particles of the element A and particles of the element B distributed therein, Wherein element A is capable of alloying with lithium, and element B is not capable of alloying with lithium, and wherein the element A is a metal or a metalloid.
13. The method according to claim 12, wherein the dispersant comprises at least one selected from the group consisting of polyvinylpyrrolidone (PVP), ethylcellulose, polyethylene glycol, and mixtures thereof, and wherein the weight percentage of the dispersant in the mixture is in the range of 0.01% to 5%. 14 . The method according to claim 12 , wherein a weight ratio of the solvent and the dispersant to the element A, the element B and the binder is in a range of 1:9 to 1:
10.
15. An electrochemical device comprising the coating of claim 1 disposed on a negative electrode.
16. The electrochemical device of claim 15, wherein the negative electrode comprises a layer of an anode active material comprising lithium metal.
17. The electrochemical device according to claim 15, further comprising a sulfide-based solid electrolyte, wherein the sulfide-based solid electrolyte comprises at least one selected from the group consisting of P2S5, Li2S-P2S5-LiX (wherein X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are each positive numbers, and Z is one selected from Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are each positive numbers, and M is one selected from P, Si, Ge, B, Al, Ga and In), Li 7-x PS 6-x Cl x (0≤x≤2), Li 7-x PS 6-x Br x (0≤x≤2), Li 7-x PS 6-x I x (0≤x≤2), and mixtures thereof.
18. The electrochemical device of claim 15, wherein the electrochemical device exhibits a capacity retention of at least 90% after 20 cycles at a discharge rate of 0.33C.
19. The electrochemical device of claim 15, wherein the electrochemical device exhibits at least 155 mAh·g after 20 cycles at a discharge rate of 0.33 C. -1 Specific capacity.
20. The electrochemical device of claim 15, wherein the electrochemical device exhibits a charge overpotential at a C-rate in the range of 1C to 5.5C that is at least 30% lower than a charge overpotential of an electrochemical device comprising an anode coating comprising an Ag / C layer at the same C-rate.